Salinity and Survival of Martesia striata (linn) in Cochin Harbour - CHERIYAN, P V; CHERIAN, C J (Fishery Technology, 2017)
The effects of salinity vanatwns on the survival of M artesia striata from Cochin Harbour are presented. It is observed that at least a few of the animals survive the low saline conditions during monsoon. Laboratory experiments showed the lethal salinity as 6 o when animals acclimatised in 34 %o were subjected to abrupt changes in salinity. But acclimatisation to 17 %o salinity showed a downward shift in the lethal salinity to 4%0• The present observations indicatethat M. striata is euryhaline arid the extent of tolerance to lower salinities depends on the degree of acclimatisation